2013
DOI: 10.1111/echo.12142
|View full text |Cite
|
Sign up to set email alerts
|

Independent Role of Left Ventricular Global Longitudinal Strain in Predicting Prognosis of Chronic Heart Failure Patients

Abstract: Quantifying LV longitudinal systolic function in CHF outpatients on the basis of 2D speckle tracking analysis provides a new parameter that independently predicts patient outcome, thus, strengthening its possible role in current clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 32 publications
4
37
0
1
Order By: Relevance
“…However, figure 3 (independent associations of all-cause mortality) shows that both studies with preserved function (Buss et al 19 and Stanton et al 6, average EF>45%), as well as most of those with impaired function (Bertini et al 11 and Sarvari et al 22, EF<45%), showed GLS to be more strongly associated than EF with outcome. Likewise, figure 5 (independent associations of composite endpoint) shows that studies by Bertini et al 11, Dahl et al 26, and Iacoviello et al 5 (EF<45%) demonstrated the hazards of impaired GLS exceed those of impaired EF, in the same way as studies showing preserved EF (Munk et al 10, Woo et al 17, average EF>45%). Thus, it appears that the risks associated with impaired GLS exceed those associated with reduced LVEF in both HF with reduced EF (HFrEF) and HF with preserved EF (HFpEF).…”
Section: Resultsmentioning
confidence: 62%
“…However, figure 3 (independent associations of all-cause mortality) shows that both studies with preserved function (Buss et al 19 and Stanton et al 6, average EF>45%), as well as most of those with impaired function (Bertini et al 11 and Sarvari et al 22, EF<45%), showed GLS to be more strongly associated than EF with outcome. Likewise, figure 5 (independent associations of composite endpoint) shows that studies by Bertini et al 11, Dahl et al 26, and Iacoviello et al 5 (EF<45%) demonstrated the hazards of impaired GLS exceed those of impaired EF, in the same way as studies showing preserved EF (Munk et al 10, Woo et al 17, average EF>45%). Thus, it appears that the risks associated with impaired GLS exceed those associated with reduced LVEF in both HF with reduced EF (HFrEF) and HF with preserved EF (HFpEF).…”
Section: Resultsmentioning
confidence: 62%
“…Myocardial strain, assessed by speckle-tracking echocardiography, measures longitudinal myocardial shortening, 32 which predicts outcomes in patients with acute myocardial infarction, 33 heart failure, 34 and after mitral valve surgery. 35 In contrast, other investigations used thermodilution cardiac indices as the primary measure of myocardial function, 18,22,36 an approach that is limited by the fact that cardiac output does not directly reflect contractile function — which may thus explain inconsistencies in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Second, patients with low LVEF (<50%) and/or HF were not enrolled in the current study, which limits the generalizability of our findings to a general hemodialysis population. However, the serum cTnT concentration [54–56] and GLS [5759] were predictive of the prognosis in nondialysis acute and chronic HF patients with varying LVEF values. Whether the measurement of cTnT concentrations or GLS or the combination thereof is also useful for risk stratification in a general hemodialysis population including patients with low LVEF and/or HF warrants further studies.…”
Section: Discussionmentioning
confidence: 99%